Addressing the Challenges and Issues of Blood Donation via Ubiquitous Computing - Dian Pradhana Sugijarto; Nurhizam Safie; Muriati Mukhtar; Riza Sulaiman (Society of Visual Informatics, 2018)
Blood is undeniably essential to save lives. The high demand for blood cannot compete with the amount collected through blood donation. In order to cater to the issue, researchers tend to focus more on the donors’ side. Meanwhile, the other party which is the blood bank continues to play its role to increase the blood supply. The blood bank processes blood in four stages: donation, screening, inventory and hospital pickup. This paper aims to address the challenges and issues in the local blood bank through ubiquitous computing, specifically at the blood donation stage. Blood donation is the most critical stage where the blood bank engages directly with the donors. The issues and challenges faced by the blood bank are uncovered by, interviews, field study and literature reviews. The proposed solution takes advantage of the ubiquitous computing concept that enables devices to communicate with each other seamlessly. With the advancement of mobile technology, smartphones become the closest of any devices to achieve ubiquitous computing. Communication technologies like Near Field Communication and Wi-Fi aid the interaction between the user and the system which are expected to solve the challenges and issues of blood donation.